Polymerization of a dual-cured cement through ceramic: LED curing light vs halogen lamp Polimerização de um cimento resinoso dual através de uma porcelana: LED vs lâmpada halógena - Lawrence Gonzaga Lopes; Eduardo Batista Franco; Abrão Name Neto; Francyle S. Herrera; Cristina Kurachi; Juan C. Castañeda-Espinosa; José Roberto Pereira Lauris (University of São Paulo, 2004)
The aim of this study was to investigate the influence of light source, LED unit and halogen lamp (HL), on the effectiveness of Enforce dual-cured cement cured under a ceramic disc. Three exposure times (60, 80 and 120 s) were also evaluated. Two experimental groups, in which the polymerization of the dual-cured cement was performed through a ceramic disc, and two control groups, in which the polymerization of the dual-cured cement was performed directly without presence of ceramic disc were subdivided into three subgroups (three different exposure times), with five specimens each: G1A- HL 60s; G1B- HL 80s; G1C- HL 120s; G2A- LED 60s; G2B- LED 80s; G2C- LED 120s; and control groups: G3A- HL 60s; G3B- HL 80s; G3C- HL 120s; G4A- LED 60s; G4B- LED 80s and G4C- LED 120s. Cement was applied in a steel matrix (4mm diameter, 1.2mm thickness). In the experimental groups, a ceramic disc was placed on top. The cement was light-cured through the ceramic by a HL and LED, however, the control groups were cured without the ceramic disc. The specimens were stored in a light-proof container at 37ºC for 24 hours, then Vickers hardness was determined. A four-way ANOVA and Tukey test (p£ 0.05) were performed. All specimens cured by LED for 60s showed inferior values compared with the halogen groups. In general, light-curing by LED for 80s and 120s was comparable to halogen groups (60s and 80s) and their control groups. LED technology can be viable for light-curing through conventional ceramic indirect restorations, when curing time is increased in relation to HL curing time. O objetivo deste estudo foi estudar a influência da fonte de luz, LED e lâmpada halógena (LH), na efetividade de polimerização do cimento resinoso dual Enforce fotoativado sob um disco de porcelana. Três tempos de exposição (60, 80 e 120 segundos) foram também avaliados. Dois grupos experimentais, na qual a polimerização do cimento resinoso foi feita através de um disco cerâmico, e dois controles, polimerização direta do cimento, sem presença do disco cerâmico foram subdivididos em três subgrupos, com cinco amostras em cada: G1A- LH 60s; G1B- LH 80s; G1C- LH 120s; G2A- LED 60s; G2B- LED 80s; G2C- LED 120s; e grupos controles: G3A- LH 60s; G3B- LH 80s; G3C- LH 120s; G4A- LED 60s; G4B- LED 80s e G4C- LED 120s. O cimento resinoso foi inserido em uma matriz de aço (4 mm de diâmetro e 1,2 mm de espessura). Nos grupos experimentais um disco de porcelana (6 mm de diâmetro por 2 mm de espessura) foi colocado sobre o cimento. Este foi fotoativado através da porcelana pela lâmpada halógena e pelo LED, por outro lado nos grupos controles a luz foi aplicada sem o disco de porcelana. As amostras foram armazenadas em um frasco que impedia a passagem de luz a 37(0)C por 24 horas, para que depois a dureza Vickers fosse determinada. Os dados foram submetidos à análise de variância a quatro critérios seguido pelo teste Tukey (p£ 0,05). Todas as amostras polimerizadas pelo LED por 60s mostraram valores inferiores quando comparadas com as do grupo da lâmpada halógena. Em geral, a fotoativação realizada por 80 e 120 s com o LED foi estatisticamente similar à fotoativação com a lâmpada halógena (60 e 80 s). A tecnologia LED pode ser viável para a fotoativação de restaurações indiretas de porcelana quando o tempo de polimerização é aumentado.